(untitled) (Bangladesh Journal of Pharmacology, 2016)
The purpose of this research work was to design and synthesize triazolyl-napthyl derivative of ?-amyrin (TNB) using click chemistry approach. The cytotoxic activity of TNB was evaluated against HK-1 human nasopharyngeal carcinoma cells using MTT cell viability assay. Fluorescence microscopy indicated cellular morphological changes induced by TNB. Flow cytometry was involved to demonstrate the effect of this compound on cell cycle and apoptosis. The results revealed that TNB inhibited in vitro cancer cell growth in dose- and time-dependent manner. The IC50 values of TNB at 24 and 48 hours time intervals were found to be 47.2 and 32.5 µM respectively. TNB-treated cells exhibited significant dense staining fragmentation called apoptotic bodies, which inferred an early apoptotic event. DNA ladder was more apparent with the increasing the TNB dose. However, no DNA fragments were observed in the control groups. TNB also induced sub-G1 cell cycle arrest and increased fraction of HK-1 apoptotic cells.